2022
DOI: 10.1001/jamanetworkopen.2022.44652
|View full text |Cite
|
Sign up to set email alerts
|

Association of Glucose-Lowering Drugs With Outcomes in Patients With Diabetes Before Hospitalization for COVID-19

Abstract: ImportancePatients with COVID-19 have a high prevalence of diabetes, and diabetes and blood glucose control are determinants of intensive care unit admission and mortality.ObjectiveTo evaluate the association between COVID-19–related adverse outcomes and 8 antihyperglycemic drugs in patients with diabetes who were subsequently diagnosed and hospitalized with COVID-19.Data SourcesData were retrieved and collected in PubMed, Embase, Cochrane Central Register, Web of Science, and ClinicalTrials.gov from database … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 69 publications
1
15
0
1
Order By: Relevance
“…Several studies have been interested in this question and a meta-analysis has shown that in diabetic patients hospitalized with COVID, serum glucose transport protein-2 inhibitors taken before the hospitalization are associated with a lower risk of a bad outcome compared to insulin, dipeptidyl peptidase-4 inhibitors or sulfonylurea. In addition, taking glucagon-like peptide-1 or metformin also seems to be associated with a better outcome [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have been interested in this question and a meta-analysis has shown that in diabetic patients hospitalized with COVID, serum glucose transport protein-2 inhibitors taken before the hospitalization are associated with a lower risk of a bad outcome compared to insulin, dipeptidyl peptidase-4 inhibitors or sulfonylurea. In addition, taking glucagon-like peptide-1 or metformin also seems to be associated with a better outcome [32].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, reliable information regarding oral hypoglycaemic medication was lacking. As it is known that such drugs are associated with lower risk of adverse effect than insulin [32], residual confounding cannot be excluded. Another risk of bias is linked to the important proportion of missing blood glucose values, which led to the exclusion of many patients.…”
Section: Limitationsmentioning
confidence: 99%
“…Benefits and risks of common medications used in metabolic syndrome management in the setting of COVID-19 are an area of intense research and discussion and have been reviewed in detail elsewhere [68] , [69] , [70] , [71*] , [72] , [73] . Data from meta-analyses [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , observational studies [25] and randomized controlled trials [84] , [85*] , [86] , [87] , [88*] , [89] have emerged while several studies are on-going. These are summarized in Table 2 .…”
Section: Preventing and Managing Covid-19 In People With Metabolic Sy...mentioning
confidence: 99%
“…[ 94a ] A meta‐analysis of 31 observational studies including more than 3.6 million COVID‐19 patients with pre‐existing T2DM, based on the surface under the cumulative ranking curves value shows that SGLT2i users had the lowest probability/possibility for adverse consequences followed by GLP1‐RA and metformin when compared to other anti‐hyperglycemic agent users. [ 97 ] More observational studies and randomized controlled trials need to be performed to shed more light on the use of SGLTi as a therapeutic drug against COVID‐19.…”
Section: Covid‐19 and Anti‐diabetic Drugs/agentsmentioning
confidence: 99%